Effect of resveratrol on chemotherapy resistance in cisplatin-induced OSCC cells through NF-κB related pathway - LI Shaopeng; YANG Haiyan; ZHANG Li; PANG Zhenzhen (Kouqiang hemian waike zazhi)
[Objective:] To observe the effect of resveratrol on the chemoresistance of oral squamous cell carcinoma (OSCC) cells induced by cisplatin (DDP), and to explore the related mechanism. [Methods:] CAL-27/DDP cells in logarithmic phase were taken and randomly divided into control group (conventionally cultured), resveratrol group (added resveratrol 200 μmol/L), agonist group [added tumor necrosis factor-α (TNF-α) 10 ng/mL], resveratrol combined with agonist group (added resveratrol 200 μmol/L, TNF-α 10 ng/mL). All groups were cultured for 48 h for subsequent experiments. The inhibition rate of cell proliferation was detected by MTT method. Double staining was used to detect the apoptosis rate. Intracellular DDP accumulation and retention were examined. Western blotting was used to detect the protein expressions of P-glycoprotein (P-gp), topoisomorases Ⅱ (Topo Ⅱ), nuclear factor-κB (NF-κB) p65, phosphorylated NF-κB (p-NF-κB) p65, inhibition of NF-κBα (IκBα) and phosphorylated IκBα(p-IκBα). [Results:] Compared with the control group, the proliferation inhibition rate, apoptosis rate, drug accumulation, drug retention, and TopoⅡprotein expression were increased, and the expression of P-gp protein, as well as the ratios of p-NF-κB p65/NF-κB p65, p-IκBα/IκBα protein expression were decreased in the resveratrol group (P<0.05). Also compared with the control group, the proliferation inhibition rate, apoptosis rate, drug accumulation, drug retention, and Topo Ⅱ protein expression were decreased, P-gp protein expression, p-NF-κB p65/NF-κB p65, p-IκBα/IκBα protein expression ratios were increased in the agonist group (P<0.05). Compared with the resveratrol group, the proliferation inhibition rate, apoptosis rate, drug accumulation, drug retention, and TopoⅡprotein expression were decreased, while the expression of P-gp protein, and the ratios of p-NF-κB p65/NF-κB p65, p-IκBα/IκBα protein expression were increased in the resveratrol combined agonist group (P<0.05). Compared with the agonist group, the proliferation inhibition rate, apoptosis rate, drug accumulation, drug retention and TopoⅡprotein expression were increased, while the expression of P-gp protein and the ratios of p-NF-κB p65/NF-κB p65, p-IκBα/IκBα protein expression were decreased in the resveratrol combined with agonist group. [Conclusion:] Resveratrol can reduce the chemotherapy of cisplatin-induced OSCC cells, and its mechanism may be related to the inhibition of NF-κB pathway.